Assessment of optimum water current velocity to improve feeding efficiency and stress response of juvenile milkfish reared in cages - Siladan, Marciel G.
response n five treatments : 0.3 ms-1, 0.5 m s-1, 0.7 m s-1, 0.9 m s-1, and 1.1 m s-1. In addition, two control groups were also tested to determine the stress during handling and acclimation period in the swimming box. Hematocrit (%) and blood glucose were used as physiological index of stress while tail beat and turning frequency were used as the behavioral index for the experiment. Feeding response to different water current treatments was also tested in 30 individuals of fish per 1 m-3 cage, in triplicates to determine the behavioral and feeding response of milkfish juveniles. Blood glucose and hematocrit were significantly higher in fish that swam at 0.9 and 1.1 m/s. Fish that were tested for handling and acclimation in the swimming bx acquired the lower blood glucose and hematocrit and were significantly different from the slower water current treatments. There were no significant difference in blood glucose among fish that swam at 0.3 m s-1 to 0.7 m s-1. The frequency of tail beat is directly proportional to the increase in water current velocity. Head turns (450) were inversely proportional to the increase in water current velocity, while downstream swimming (3600) showed erratic results in the experiment. Rheotactic behavior was also observed prior to and during the feeding experiment. The movement of milkfish juveniles in this experiment, to some extent, were similar to the behavior of fish that were tested for the sustained swimming exercise. Based on the amount of eaten feeds, fish positively responded, albeit with no significant difference, during the feeding experiment in all water current treatments. This study shows that in terms of physiological and behavioral responses, milkfish can tolerate water current velocities from 0.3 m s-1 to 0.7 m s-1 with minimal stress. However, feeding response in terms of feed consumed indicates that all velocities tested could be suitable although in terms of fish behavior during feeding, currents of up to 0.5 m s-1 influences fish to occupy a larger volume of the cage thus maximizing the entire water column for feeding. With these results, it can be concluded that water current velocities of up to 0.5 m/s would be optimal for rearing milkfish in cages.